Cardioprotective role of signal transducer activator of transcription 3 (STAT-3) against ischaemai reperfusion injuries - King, Jonathan Chan (Division of Cardiology, 2015)
Introduction: Sphingosine 1 phosphate (S1P) is a major constituent of high density lipoprotein (HDL) cholesterol. Both S1P preconditioning and ischaemic postconditioning reduce myocardial damage following an ischaemia-reperfusion insult but the mechanisms involved remain unclear. Janus kinase/Signal transducer and activator of transcription 3 (JAK/STAT-3) form part of a recently discovered powerful prosurvival path termed as the Survivor Activating Factor Enhancement (SAFE) pathway. The SAFE pathway plays a critical role in ischaemic preconditioning to promote cell survival but whether activation of STAT-3 is required for S1P preconditioning and ischaemic postconditioning induced cardioprotection is unknown. Hypothesis: Activation of the STAT-3 is required for S1P preconditioning and ischaemic postconditioning.